Composición y distribución de la ictiofauna en la Laguna del Mar Muerto, Pacífico mexicano - Tapia-García, M; Suárez Núñez, C; Cerdenares L. de Guevara, G; Macuitl Montes, M C; García Abad, M C (Revista de Biología Tropical, 1998)
Fish composition was sampled in Mar Muerto Lagoon (Mexico) between 1991 and 1993. A total oC 27 971 fish with a weight oC 120.9 kg were collected. The total sample consists oC 29 Camilies, 45 genera and 66 species. The highest number of species is in tbe area with strong marine influence (near Tonala InIet), abundant coastal vegetation and fluvial discharge. The lowest number oC species is in the inner part oC the lagoon, which is hipersaline in the dry season and of low salinity in the rainy season. The species witli broad distribution are Diapterus peruvianus, Lile stolifera, Anchoa lucida, Anchoa mundeola, Mugil curema, Atherinella guatemalensis and Anchovia macrolepidota.